Approximate analytical models for microsegregation considering the effect of dendrite arm coarsening - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
In this study, simple analytical microsegregation models for constant cooling and parabolic growth are proposed considering dendrite arm coarsening effect with and without back diffusion. These simple models are compared with the Mortensen exact model and Voller's models. It is shown that these analytical models can be used to predict approximately microsegregation in a binary alloy.
Keywords: microsegregation; dendrite arm coarsening; back diffusion; dendritic solidification; modeling; SOLUTE REDISTRIBUTION; SOLIDIFICATION